Les dispositifs optiques au XIXe siècle et la production des images dans Madame Bovary - Jeanne Bem (Flaubert: Revue Critique et Génétique)
When Flaubert began writing Madame Bovary, around 1850, literature was focusing on the “visible” world. This development paralleled the recent emergence of photography, which was only one of the many optical devices appearing alongside scientific advances dealing with perception. Drawing on the writings of Jonathan Crary and Rosalind Krauss, I argue that Flaubert (who, in addition, had had personal experiences with hallucinatory visions) was not primarily attracted to the idea of the artist as a “realist.” Instead, he considered himself as a visual artist, a producer of autonomous images. I focus on an episode in his novel Madame Bovary, a short text called “Les Verres de couleur”, which has remained at the draft stage in several manuscript versions. I show how Flaubert set up an art installation for his heroine, and how, by letting her experiment with colored vision, he transferred some of his curiosity and creativity onto her.